UKRAINE’S FOREIGN TRADE WITH THE EU: OPPORTUNITIES AND CHALLENGES - ARTAMONOVA, Halyna (Journal of European Economy, 2019)
The article casts light onto the current state of foreign trade between Ukraine and the EU in the conditions of a free trade area. Having analyzed the structure of merchandise exports and imports, the author reveals major challenges that arise as current tendencies persist into the future. Special attention is paid to seizing the opportunities provided by the EU-Ukraine Free Trade Agreement for realization of export potential of the agricultural sector on the markets of these countries. The author suggests ways to create conditions for diversification of merchandise exports, facilitation of access to European markets for the exporters of finished agricultural goods, as well as taking measures for constraining the inflows of non-critical merchandise imports, in particular pharmaceutical products. JEL: F10, F13, F68.